Developing a novel toffee-type soft candy process by sonocrystallization: A preliminary study - Kopuk, Berkay; Gunes, Recep; Polat, Derya Genc; Tasan, Murat; Kurultay, Sefik; Palabiyik, Ibrahim; Toker, Omer Said; Konar, Nevzat; Elobeid, Tahra (ELSEVIER, 2024)
This study aimed to evaluate the applicability of sonocrystallization, an innovative process, as a low-cost and time-efficient alternative for the crystallization of confectionery dough, which is a crucial step in the production of conventional toffee-type soft candy. In this regard, according to the design plan, sonocrystallization time and current were selected as independent variables. The samples (36 run) nucleated by sonocrystallization using the optimum conditions (1600 and 2400 mA, 20 min) were allowed to aging under different times (0, 2, 4, 6, 8, and 10 min) and temperatures (60, 65, and 70 degrees C) in order to determine crystal growth. According to the texture profile analysis results, all parameters except for cohesiveness were significantly affected by both the sonocrystallization and aging conditions (p 65 degrees C for durations of >6 min. The targets of the study were achieved by subjecting the samples to sonocrystallization at 2400 mA and aging at 70 degrees C for 8 min for crystal growth.
Keywords: Sonocrystallization; Confectionery; Soft candy; Nucleation; Crystallization; PARTICLE-SIZE; ULTRASOUND; TEXTURE; ISOMALTULOSE; MOISTURE; RELEASE; STARCH; SUGARS; Food Science & Technology